Makna Reformasi Hukum Bagi Pelaku Bisnis di lndonesia - mudjiono mudjiono (Jurnal Hukum IUS QUIA IUSTUM, 2004)
Reformation in law brings a significant influence for businessman in Indonesia. The alteration of a iegai direction wiil bring a policy atteration ofbusiness, in view o fthat, itis need to base the alteration on a good management strategy to prevent a monetary fluctuation as occurred in the past that caused by uncompatibie government legal policy